Three Generations of Belarusian Historical Fiction in Prose and Verse: Inspiration and Iconoclasm - McMillin, Arnold (Przegląd Wschodnioeuropejski, 2023)
Beginning with attempts to deny or repress the very idea of Belarusian history, this article is devoted the use of historical themes by three generations of Belarusian writers, with the youngest first and ending with three from the middle generation who, as a rule, do not show the influence of their elders on themselves, nor do they seem greatly to influence the younger writers. All ages, however, are engaged in the same struggle to counter the anti-historical ideas propagated by the leadership of their country, and the younger writers bring a sometimes unusual, indeed iconoclastic, approach to this important task.